2018
DOI: 10.1159/000489121
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Rate in First-Trimester Screening Based on Ultrasound and Cell-Free DNA versus First-Trimester Combined Screening with Additional Ultrasound Markers

Abstract: Objective: To determine whether screening for trisomy 21 based on first-trimester combined screening (FTCS) with assessment of nasal bone (NB), tricuspid flow (TCF), and ductus venosus flow (DVF) results in similar false-positive rates compared to ultrasound and cell-free DNA (cfDNA) screening. Methods: This is a subanalysis of a prospective randomized controlled trial which was performed between October 2015 and December 2016. Pregnant women with a normal first-trimester ultrasound examination at 11 to 13 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For over a decade, the first-trimester combined test, including maternal age, fetal NT and maternal serum biochemistry, with a detection rate of 90% at a FPR of 5%, has played a major role in screening for trisomy 21 in the first trimester of pregnancy. In recent years, cell-free (cf)DNA testing has improved significantly the performance of screening for trisomy 21, with a detection rate of > 99% at a FPR of < 0.1% [21][22][23][24] . However, the cost of cfDNA testing is high, making it impossible to offer it to all pregnant women.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…For over a decade, the first-trimester combined test, including maternal age, fetal NT and maternal serum biochemistry, with a detection rate of 90% at a FPR of 5%, has played a major role in screening for trisomy 21 in the first trimester of pregnancy. In recent years, cell-free (cf)DNA testing has improved significantly the performance of screening for trisomy 21, with a detection rate of > 99% at a FPR of < 0.1% [21][22][23][24] . However, the cost of cfDNA testing is high, making it impossible to offer it to all pregnant women.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…3,4 However, some studies have suggested that further cost-saving approaches should be explored, considering the potentially high cost of cell-free fetal DNA testing. 4,5 For decades, ultrasonographic images have been widely used for screening fetuses for trisomy 21, owing to the advantages of safety, convenience, and low cost. 6,7 Fetal nuchal translucency (NT) thickness, measured in ultrasonographic images, has been used to screen fetuses with trisomy 21.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, analyses of cell-free fetal DNA validation show high accuracy (up to 99%) in screening for trisomy 21 . However, some studies have suggested that further cost-saving approaches should be explored, considering the potentially high cost of cell-free fetal DNA testing …”
Section: Introductionmentioning
confidence: 99%
“…Women in their first 3 months of pregnancy are offered first trimester combined screening (FTCS), based on maternal age, fetal nuchal translucency thickness (NT) and serum markers such as beta human chorionic gonadotropin (β-HCG) and pregnancy-associated plasma protein A (PAPP-A), with a detection rate for T21 of 90–95% and a false positive rate of 2.5–5% ( Kagan et al, 2019 ), as well as a positive predicted value of 3.4% ( Norton et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%